TRIBOLOGICAL IMPLICATIONS OF THP MODULARIZATION - Lucian CAPITANU; Liliana-Laura BADITA; Constantin TIGANESTEANU (Proceedings on Engineering Sciences, 2019)
The aim of the paper is to highlight the advantages of the modularization of the femoral component of the Total Hip Prosthesis (THP), especially the tribological implications it presumes (fretting wear of the modular junctions, fatigue and corrosion by fretting, which can contribute to the increase of metal ions concentrations in the blood and the possibility of the femoral stem fracture at the femoral head junction). Experimental laboratory studies focused on the analysis of the tribological phenomena occurring at the conical junctions between the femoral head and neck, as well as the neck and femoral stem, highlighting the relevant qualitative tribological aspects. Femoral stems with two junctions allow even greater capacity for the independent fit of the proximal femoral, offset and limb length with the metaphysical dimension/ stem body. For this purpose, experimental junctions, tested on a universal MTS testing machine, were built. It emphasizes the importance of the materials used for the conical or trapezoidal joints components and the measures to reduce the micro-motion that lead to fretting phenomena and fretting corrosion. The influence of conicity on the tribological phenomena is analysed.